Perisciatic Injection of Steroid for the Treatment of Sciatica due to Piriformis Syndrome. Issue 2 (March 1998) - Hanania, Michael; Kitain, Eric
Abstract : Background and Objectives: Piriformis syndrome causing sciatica is sometimes refractory to conventional treatments including physical therapy, piriformis injections, and even caudal epidural steroid injections. Surgical release of the piriformis muscle has been described for difficult cases of piriformis syndrome, but is occasionally accompanied by morbidity. Another approach to treating piriformis syndrome is presented. Methods: A perisciatic injection of steroid using simple landmarks and utilizing a nerve stimulator to locate and inject near the sciatic nerve and into the piriformis muscle is described. Results: Six patients that did not respond to conventional treatments, but did respond to perisciatic steroid injections are presented. CT scan, in one of the patients, confirmed correct needle placement when this technique and landmarks were used. Conclusion: Patients with piriformis syndrome who were refractory to conventional treatments but responded to perisciatic injections of steroid are presented.